Avaliação da intenção de uso do preservativo entre adolescentes participantes e não participantes de projetos educativos nas escolas - Oliveira, Simone Helena dos Santos (2009)
Facing AIDS problem in adolescence and regarding the use of condom as of essential importance in its prevention, in a way that this behavior can be promissory when induced by actions in health education developed at school, it was made this present research, which goal was to evaluate the behavioral intention with the use of condom in sexual intercourse, and its determinants among adolescents participating an non-participating in educational health actions at school related to prevent AIDS. It is a quantitative research that used the Theory of Reasoned Action – TRA. The research was taken in two Public Schools, in João Pessoa, with adolescents from 13 to 19 years old, both sexes, from 7th grade in Fundamental level to 3rd grade of High School. It was taken in two steps. On 1st step, a form was filled to make a survey of behavior beliefs and pronounced modal standard. On 2nd step, a test based on the beliefs identified on step 1, made of Likert Type Schools, was applied to 566 students. Data was analyzed from different statistic tools: absolute frequency and percentage, mean, standard mean, Cronbach Alpha coefficient, Pearson correlation coefficient r, Multiple Regression by steps. The results from first step brought up the same categories of positive pronounced modal behavior standards in both schools (STD, pregnancy and AIDS prevention). Among all adolescents from both schools, troublesome, less pleasure and rupture risk were the pointed handicaps on using condoms. Positive standards beliefs were mothers, fathers and friends who were pointed by adolescents from both schools. Negative modal standard beliefs were less frequent comparing to positive, friends and cousins were named by adolescents from schools A and B, and brothers and uncles only from the ones of school B. The behavior intention of using condom was positive in both groups researched, but mean was a discretely higher among adolescents from School A. Expressive evidence correlated behavior and standard components as a measure of intentional behavior in both schools. Four independents variables contributed significantly to explain the variance of intention of using condoms in school A, but subjective standard presented more powerful explanation for the behavior studied. Among adolescents from school B, it was verified that behavior beliefs, subjective rule and stance explain the intention in using condoms, but behavior beliefs came to be stronger. The results showed stances and rules that sustain the intention in using condoms, as well as beliefs that build those stances and rules, which can give subsidies to planning strategies aiming sexual health care and put in evidence to validate TRA to work the proposed subject.